Women’s Power To Be Loud: The Authority of the Discourse and Authority of the Text in Mary Dorcey’s Irish Lesbian Poetic Manifesto “Come Quietly or the Neighbours Will Hear” - Poloczek, Katarzyna (Text Matters: A Journal of Literature, Theory and Culture, 2011)
The following article aims to examine Mary Dorcey's poem "Come Quietly or the Neighbours Will Hear," included in the 1991 volume Moving into the Space Cleared by Our Mothers. Apart from being a well-known and critically acclaimed Irish poet and fiction writer, the author of the poem has been, from its beginnings, actively involved in lesbian rights movement. Dorcey's poem "Come Quietly or the Neighbours Will Hear" is to be construed from a perspective of lesbian and feminist discourse, as well as a cultural, sociological and political context in which it was created. While analyzing the poem, the emphasis is being paid to the intertwining of various ideological and subversive assumptions (dominant and the implied ones), their competing for importance and asserting authority over one another, in line with, and sometimes, against the grain of the textual framework. In other words, Dorcey's poem introduces a multilayered framework that draws heavily on various sources: the popular culture idiom, religious discourse (the references to the Virgin Mary and the biblical annunciation imagery), the text even employs, in some parts, crime and legal jargon, but, above all, it relies upon sensuous lesbian experience where desire and respect for the other woman opens the emancipating space allowing for redefining of one's personal and textual location. As a result of such a multifarious interaction, unrepresented and unacknowledged Irish women's standpoints may come to the surface and become articulated, disrupting their enforced muteness that the controlling heteronormative discourse has attempted to ensure. In Dorcey's poem, the operating metaphor of women's silence (or rather—silencing women), conceived of, at first, as the need to conceal one's sexual (lesbian) identity in fear of social ostracism and contempt of the "neighbours," is further equated with the noiseless, solitary and violent death of the anonymous woman, the finding of whose body was reported on the news. In both cases, the unwanted Irish women's voices of either agony, during the unregistered by anybody misogynist bloodshed that took place inside the flat, or the forbidden sounds of lesbian sexual excitement, need to be (self) censored and stifled, not to disrupt an idealized image of the well-established family and heteronormative patterns. In the light of the aforementioned parallel, empowered by the shared bodily and emotional closeness with her female lover, and already bitterly aware that silence in discourse is synonymous with textual, or even, actual death, the speaker in "Come Quietly or the Neighbours Will Hear" comes to claim her own agency and makes her voice heard by others and taken into account.